Dysmorphological Delineation of Orofaciodigital Syndrome Type I. Presentation of a Case and Literature Review - Noel Taboada Lugo; Ana María Rodríguez Díaz; Tairí Borges García (Revista Finlay)
Orofaciodigital syndromes are a heterogeneous group of developmental disorders, of which at least 18 clinical variants have been described. Type I or Papillon-Leage Psaume syndrome is transmitted with lethal X-linked dominant inheritance. The case of a seven-year-old patient with a history of delayed psychomotor development and moderate intellectual disability is presented, in which a dysmorphic pattern was found due to thin and sparse hair, hypotrichosis with alopecic areas, bilateral epicanthal fold, pseudohypertelorism due to the presence of telecanthus, severe dental malpositions, transverse micrognathism, as well as other anomalies. The presence of facial, oral and digital dysmorphisms allowed the diagnosis to be made through the clinical method, given the absence of family history that would explain the presence of the disease as a result of a new mutation. Its interest lies in presenting the phenotypic delineation of a rare syndrome, which can manifest with a mild clinical expression or associated with important dysmorphological alterations.